3D organotypic cell structures for drug development and Microorganism-Host interaction research - Ekaterina V. Zubareva; Sergey V. Nadezhdin; Natalia A. Nadezhdina; Veronika S. Belyaeva; Yuriy E. Burda; Tatyana V. Avtina; Oleg S. Gudyrev; Inga M. Kolesnik; Svetlana Yu. Kulikova; Mikhail O. Mishenin (Belgorod National Research University, 2021)
Introduction: The article describes a new method of tissue engineering, which is based on the use of three-dimensional multicellular constructs consisting of stem cells that mimic the native tissue in vivo - organoids. 3D cell cultures: The currently existing model systems of three-dimensional cultures are described. Characteristics of organoids and strategies for their culturing: The main approaches to the fabrication of 3D cell constructs using pluripotent (embryonic and induced) stem cells or adult stem cells are described. Brain organoids (Cerebral organoids): Organoids of the brain, which are used to study the development of the human brain, are characterized, with the description of biology of generating region-specific cerebral organoids. Lung organoids: Approaches to the generation of lung organoids are described, by means of pluripotent stem cells and lung tissue cell lines. Liver organoids: The features of differentiation of stem cells into hepatocyte-like cells and the creation of 3D hepatic organoids are characterized. Intestinal organoids: The formation of small intestine organoids from stem cells is described. Osteochondral organoids: Fabrication of osteochondral organoids is characterised. Use of organoids as test systems for drugs screening: The information on drug screening using organoids is provided. Using organoids to model infectious diseases and study adaptive responses of microorganisms when interacting with the host: The use of organoids for modeling infectious diseases and studying the adaptive responses of microorganisms when interacting with the host organism is described. Conclusion: The creation of three-dimensional cell structures that reproduce the structural and functional characteristics of tissue in vivo, makes it possible to study the biology of the body's development, the features of intercellular interactions, screening drugs and co-cultivating with viruses, bacteria and parasites.